Full Account of the Costs and Benefits of Reducing CO2 Emissions in Transport - Proost, Stef (OECD Publishing, 2008)
Among economists and policy makers more general, the fuel efficiency standard for cars and the fuel tax have been the subject of extensive debate. The major benefits of stricter fuel efficiency standards and higher fuel taxes are the reduction of Greenhouse gas emissions and the reduced oil dependence. The major costs are the increased production cost, the reduced comfort and the negative impact on mileage related externalities (congestion, accidents) due to the rebound effect. In this contribution we use a wider framework than Harrington (2008), Plotkin (2008) and Raux (2008) to discuss the CO2 1 emission reduction in transport. In section 2 we analyze, for the EU, the effects on welfare and CO2 emissions of pricing all transport activities according to their full social costs. In section 3, we go beyond the transport sector and compare the options to reduce emissions in the transport sector with the possibilities and costs to reduce emissions in other sectors of the economy. In section 4 we take a world view and analyze the impact of two types of international climate negotiations on the emission reduction strategy in the transport sector
Keywords: Transport